-
If x = 2015, y = 2014 and z = 2013, then value of x2 + y2 + z2 – xy – yz – zx is
-
- 3
- 4
- 6
- 2
- 3
Correct Option: A
x – y = 2015 – 2014 = 1
y – z = 2014 – 2013 = 1
z – x = 2013 – 2015 = –2
∴ x2 + y2 + z2 – xy – yz – zx = | [ 2x2 + 2y2 + 2z2 – 2xy – 2yz – 2zx ] | |
2 |
⇒ x2 + y2 + z2 – xy – yz – zx = | [ x2 + y2 – 2xy + y2 + z2 – 2yz + z2 + x2 – 2zx ] | |
2 |
⇒ x2 + y2 + z2 – xy – yz – zx = | [ (x - y)2 + (y - z)2 + (z - x)2 ] | |
2 |
⇒ x2 + y2 + z2 – xy – yz – zx = | [ (-1)2 + (-1)2 + (2)2 ] | |
2 |
⇒ x2 + y2 + z2 – xy – yz – zx = | [ 1 + 1 + 4 ] | |
2 |
⇒ x2 + y2 + z2 – xy – yz – zx = | × 6 = 3 | |
2 |